Lichens as promising resources of enzyme inhibitors: A review - Prashith Kekuda, T.R; Lavanya, D; Pooja, Rao (Journal of Drug Delivery and Therapeutics, 2019)
Inhibition of some enzymes seems to be one of the therapeutic strategies for the management of certain diseases or conditions such as diabetes, Alzheimer’s disease, cancer and obesity. In this review, an updated information on the enzyme inhibitory activity of lichen extracts and lichen compounds by an intensive literature survey is presented. Crude solvent extracts and isolated compounds from lichens were shown to be effective in causing inhibition of several enzymes such as amylase, lipase, lipoxygenase, aromatase, cyclooxygenase, trypsin, β-glucoronidase, prolyl endopeptidase, monoamine oxidase, urease, tyrosinase, xanthine oxidase, Thioredoxin reductase, glucosidase, topoisomerase, pancreatic elastase, phosphodiesterase, telomerase and acetylcholinesterase. Lichen metabolites such as usnic acid and its derivatives, lobaric acid, physodic acid, ramalin, protolichestrinic acid, salazinic acid, atranorin, evernic acid, zeorin, diffractic acid, psoromic acid, methyl β-orcinolcarboxylate, methylorsellinate, and anziaic acid were shown to be inhibitors of some enzymes. In conclusion, lichens can be employed as promising therapeutic agents in terms of their potential to inhibit the activity of certain enzymes that are involved in some diseases or disorders. In vitro culturing of lichen symbionts in optimized media can be carried out to isolate enzyme inhibitors in larger scale and to develop effective therapeutic agents. Keywords: Lichens, lichen substances, enzyme inhibitors, enzyme inhibitory activity